(untitled) (Web of Teachers: Inderscience Research, 2024)
This article reveals the main opportunities for the effective development of culture among cadets by means of a foreign (English) language through the implementation of pedagogical technology. The article presents the importance of the technology for the development of speech culture among cadets in the process of teaching a foreign language (English), the main goals of the technology are outlined. The article notes the importance of the inviolability of correlations in determining the goal and the development of the content of the technology with the goals and content of teaching a foreign language characteristics, the tasks of the teacher for the development of speech culture among cadets, the formation of a value-based attitude to the native (Uzbek) language of cadets for mastering speech skills and the rules of speech interaction are determined. The author comes to the conclusion that the combination of culturological, socio-linguistic and professionally-oriented content of the content of the pedagogical technology for the development of speech culture among cadets in the process of teaching a foreign language contributes to their value-based attitude to their native culture and native language and a stable motivation to improve their cultural and speech level.